1998
DOI: 10.1038/2530
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene knockout mediated by triple helix forming oligonucleotides

Abstract: Triple helix forming oligonucleotides (TFOs) recognize and bind sequences in duplex DNA and have received considerable attention because of their potential for targeting specific genomic sites. TFOs can deliver DNA reactive reagents to specific sequences in purified chromosomal DNA (ref. 4) and nuclei. However, chromosome targeting in viable cells has not been demonstrated, and in vitro experiments indicate that chromatin structure is incompatible with triplex formation. We have prepared modified TFOs, linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 31 publications
5
118
0
1
Order By: Relevance
“…This finding expands our understanding of both the recognition of distorted DNA structures by NER, and the processing of triplexes by NER that may contribute to the triplex-induced mutagenesis reported by our group and others (27,30,34,35,(52)(53)(54)(55)(56)(57)(58). In addition, both in vitro and in vivo studies have revealed a role for XPA in the induction of recombination by triple helix formation (28,29).…”
Section: Dna Damage Recognitionmentioning
confidence: 69%
“…This finding expands our understanding of both the recognition of distorted DNA structures by NER, and the processing of triplexes by NER that may contribute to the triplex-induced mutagenesis reported by our group and others (27,30,34,35,(52)(53)(54)(55)(56)(57)(58). In addition, both in vitro and in vivo studies have revealed a role for XPA in the induction of recombination by triple helix formation (28,29).…”
Section: Dna Damage Recognitionmentioning
confidence: 69%
“…Inoue et al, have reported that 2'-O-methyloligoribonucleotide derivatives are not subject to cleavage by RNase H, and that a 2'-O-methylribonucleotide:RNA duplex is thermally more stable than an RNA:RNA duplex [76]. 2'-O-methylribose (2'-OMe) and 2'-O-aminoethylribose (2'-AE) modified oligonucleotides have been synthesized and successfully used to induce mutations in cells via the formation of DNA:DNA:RNA triple helices [77,78]. Interestingly, extensive modification of TFOs with 2'-OMe and 2'-AE residues leads to increased binding affinity in vitro, but reduced activity in vivo [79].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…Moreover, the interaction of TnsC with triplex DNA motifs may uncover further information protein recognition of triple-helical nucleic acids, providing new evidence of their potential biological roles. Although many useful applications for triplex DNA have been found over recent years (27,(45)(46)(47), their biological role remains to be demonstrated. is illustrated.…”
Section: Discussionmentioning
confidence: 99%